Asset Forfeiture through Non-Conviction Based Asset Forfeiture and Management of Criminal Proceeds Assets: A Comparative Study with the United States and Thailand - Anisa, Tasya; Nelson, Febby Mutiara (Faculty of Law, Universitas Pekalongan, 2024)
Confiscation is based on the principle that the proceeds of crime must be confiscated, because the convicted person should not benefit from the crime he committed. The procedure for handling confiscated property is something that needs to be regulated. So it is very important in a rule to determine who is responsible for taking the seized goods and holding them, where they should be stored, and what will be done with them. This paper compares and contrasts the NCB non-conviction based asset forfeiture rules owned by Indonesia, the United States and Thailand as well as the responsibilities in managing assets based on the results of confiscation and confiscation owned by these countries. The selection of the United States as a comparison country in this paper is based on the fact that countries that adhere to the common law legal system have commonly practiced the concept of NCB asset forfeiture as an activity in confiscating and seizing assets and the United States has been implementing the concept for decades. While in the Southeast Asian region, Thailand is one of the countries that has long implemented the concept of NCB asset forfeiture and has an independent institution